Electrochemical growth of Co(OH)2 nanoflakes on Ni foam for methanol electro-oxidation. (7th August 2017) - Roy, Animesh; Jadhav, Harsharaj S.; Thorat, Gaurav M.; Seo, Jeong Gil
Abstract : Co(OH)2 nanoflakes directly grown on Ni foam using an electrodeposition route exhibit a promising performance for electrocatalytic oxidation of methanol. Abstract : Recently, direct methanol fuel cells (DMFCs) have been considered as one of the most promising energy sources for portable devices and transportation applications. Herein, cobalt hydroxide (Co(OH)2 ) nanoflakes were directly grown on a conducting Ni foam substrate via an electrodeposition route. Electrodeposition technique is an excellent method in which active materials can be directly grown on a substrate without the addition of any binder and conducting agent. The hydroxide was deposited from 0.05 M aqueous cobalt nitrate electrolyte at −0.75 V vs. SCE without the addition of any surfactant. Co(OH)2 showed excellent electrocatalytic activity with a superior long-standing stability towards electro-oxidation of methanol. The observed current density of Co(OH)2 in 1 M KOH with 0.5 M methanol was 150 A g −1 at the scan rate of 10 mV s −1 . The onset potential of methanol oxidation for the Co(OH)2 catalyst was found to be 0.27 V. The excellent electrocatalytic properties of the electrocatalyst are mainly attributed to the direct growth of an electroactive nanostructure that enhances mechanical adhesion and facilitates a fast electron transfer between the current collector and the electrocatalyst.